A new tribe of scaphocephalic Achilidae from South Africa (Hemiptera: Fulgoromorpha) - Alicja M. Brysz; Adam Stroiński; Jacek Szwedo (European Journal of Taxonomy, 2024)
This paper describes a new genus and species of Achilidae (Hemiptera: Fulgoromorpha) Achiplecton stilleri gen. et sp. nov from the newly established tribe Achiplectini trib. nov. This tribe belongs to one of three Achilidae subfamilies, Myconinae, and is found solely in the West Cape of Southern Africa. The whole region is thought to be one the of the Earths most biologically diverse areas, also characterized by the phylogenetic antiquity of its invertebrates. Morphological peculiarities of the new achilids are discussed, especially modification of the head capsule presenting the ‘laternarisation syndrome’, which is unique in Achilidae, and tegmina modifications, without the postclaval lobe overlapping.